About Role Models Derived from Classical Authors in the 18th- and 19th-century Poland - Brzuska, Barbara (In Gremium. Studies in History, Culture and Politics, 2019)
The nineteenth century in Poland brought about a surge in the number of translations from Latin and Greek, which resulted from the diminishing number of people who were able to read Greek and Latin classics in the original languages, on the one hand, and on a widely held conviction about extraordinary formative qualities of this literature in the process of educating young people, on the other. The changing political situation in the country and the evolving literary tastes were both key factors influencing the choice of authors to be translated as well as the way their works were being read or interpreted, and impacting the role models and examples of civic virtue that were picked out as worthy of promulgating. At the same time, however, there appeared a number of anti-heroes from Antiquity who were not always that ‘obvious,’ and sometimes downright surprising – and some attitudes that we would not be so quick to condemn today were nevertheless rejected, or even abhorred, by some people living in the 19th century. The goals that the translators of classical literature in Poland set for themselves and often laid out in the prefaces or introductions to their translations, as well as opinions expressed in book reviews appearing in the 19th-century press in conjunction with theoretical reflexion on the functions of translation are all meant to serve as material for this article.